Mems based integrated temperature and humidity sensor for agricultural monitoring - Priyadarisshini, B; Sindhaniselvi, D; Shanmuganatham, T (International Journal of Engineering and Technology, 2018)
Temperature and Humidity are interrelated parameters in the agricultural field to monitor the growth of the crop. This paper is proposed to design the MEMS based integrated temperature and humidity sensor for the cardinal temperature range of 35°F to 105°F and the relative humidity range of 60 % to 100% which is suitable for cultivating crops range in our country. These interrelated parameters are to be main-tained for the better quality and high yield of the crop in the agricultural field. The integrated sensor is designed using simple cantilever and its analyzed. Further, sensitivity is enhanced with perforation in the sensing layer and dielectric layer and ribs in the dielectric layer.